The Perception of Information Technology (Social-Media) in Micro, Small, and Medium Enterprises (MSMEs): A SWOT Analysis - Nuri, Siti Nuran; Nurita Andriani (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2024)
The trend of digitalization is affecting commerce around the world. Previously traditional marketing methods have now been integrated into the digital world. Information and Communication Technology (ICT) is important for carrying out business activities, especially in Micro, Small and Medium Enterprises (MSMEs). This study aims to analyze the use of social media as a marketing tool for MSMEs in Bangkalan District. The method used is SWOT analysis (strength, weakness, opportunity, and threat). Qualitative data in the form of questions asked to research respondents using a questionnaire with 30 respondents from MSMEs in Bangkalan District, then the data is quantified so that it can be analyzed more deeply. The results obtained by MSMEs in utilizing social media as a marketing medium based on the SWOT quadrant diagram are in quadrant I, which means that the strategy used is a growth strategy, namely the SO strategy. This strategy uses strengths to take advantage of opportunities that exist in MSMEs. The implementations are to use various social media platforms effectively, increase the intensity of marketing/promotion through good cooperation with influencers for endorsement content, market development to e-commerce, strengthen or maintain existing relationships with consumers, maintain product and service quality, create interactive, entertaining, emotional, and informative content.